Menerapkan Pembelajaran Bahasa Arab Pada Maharah Kitabah Dengan Strategi Guided Composition - Syarifah Aulia; Siti Nur Fadhilah; Sari Annisa Siregar; Robbi Reyhan Chandra; Sahkholid Nasution (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
One of the important skills for learning Arabic is the ability to write, or mahar al-kitabah. The purpose of this paper is to discuss the theories that support the scientific learning of Arabic writing skills. Methodologically, this paper is descriptive qualitative by investigating various relevant sources. The results of the study show that mastery of linguistic elements such as vocabulary, grammar, and writing rules is necessary to master writing skills. Students must also go through various steps, such as modeling, getting guidance, and independent writing, to achieve the learning objectives. By understanding this idea, it is hoped that the learning and teaching of maharah al-kitabah can be improved in educational institutions.